Nationalism will never die: Zimbabwean discourses in the global age - Vhutuza, Ephraim (2016)
This paper explores the relevance of the institution of nationalism in Zimbabwe in today's globalised world in the wake of calls by Postmodernists for a post-national age' following the fall of the colonialist enterprise in Africa and the demise of the bipolar world. To these scholars, nationalism has become anachronistic and its rightful place, the dustbins of history. This paper however, argues that nationalism as a multifaceted and agile institution, mutates and transforms into different forms at different stages in the history of a people in space and time though admittedly, as demonstrated by the Zimbabwean nationalist discourses case study, it can produce its own denial.Without necessarily debating its merits or demerits, the paper argues that nationalism will continue lobe relevant as long as people live and question injustices and or simply, attempt to redefine themselves in today's drive towards global identities.